Decreased flow‐mediated dilation in gestational diabetes in pregnancy and post‐partum. A systematic review and meta‐analysis. Issue 2 (20th December 2022) - Chatzakis, Christos; Koletsos, Nikolaos; Tirta, Maria; Dinas, Konstantinos; Gkaliagkousi, Eugenia; Sotiriadis, Alexandros
Abstract: Aims: Gestational diabetes mellitus (GDM) is a common medical complication during pregnancy. Endothelial dysfunction is considered an early step in the progression of atherosclerosis that may contribute to subclinical target organ damage. This meta‐analysis aimed to systemically review the existing data regarding endothelial dysfunction between women with and without GDM during pregnancy and post‐partum using flow‐mediated dilation (FMD). Materials and Methods: Eligible studies (cohort and observational) published until October 2021 were identified in the MEDLINE, Scopus, Cochrane Library database and grey literature sources were searched. Results: The search yielded 2272 studies, of which 17 were fully reviewed and 12 studies ( N = 740 pregnant women) were finally included. Pregnant women with GDM exhibited a significantly lower FMD compared to pregnant women without GDM (pooled mean difference −3.12; 95% CI −5.36 to −0.88). Moreover, in the immediate (1–6 months) post‐partum period, women with previous GDM showed lower FMD compared to healthy women without GDM history (pooled mean difference −7.52; 95% CI −9.44 to −5.59), whereas FMD did not differ in the late post‐partum period (more than 4 years). Conclusions: Flow‐mediated dilation is decreased in women with GDM during pregnancy and in the immediate post‐partum period, compared to women without GDM, indicating that the endothelial dysfunction noted during the pregnancy in those women persists in the immediate post‐partum period too. Clinical trial registration: PROSPERO CRD42021283113 (www.ClinicalTrials.gov ).